1999
DOI: 10.1007/bf02464298
|View full text |Cite
|
Sign up to set email alerts
|

Ectomycorrhiza formation of Tricholoma matsutake on Pinus densiflora

Abstract: Mycorrhizal association of Tricholoma matsutake with Pinus densiflora was studied. A naturally established P. densiflora stand (age: ca. 45 yr) where occurrences of T. matsutake sporocarps had been confirmed was studied in Ibaraki Prefecture, Japan. Pine root systems connected with T. rnatsutake sporocarps via the fungal white mycelia were sampled in October 1997. The sampled pine roots were covered overall with white mycelia. Under a dissecting microscope, the mycelia were confirmed to form fungal sheaths on … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
41
0

Year Published

1999
1999
2021
2021

Publication Types

Select...
4
3

Relationship

4
3

Authors

Journals

citations
Cited by 57 publications
(43 citation statements)
references
References 7 publications
2
41
0
Order By: Relevance
“…We have demonstrated here that T. matsutake forms an ectomycorrhizal association with its host P. densiflora, in concurrence with Yamada et al (1999) and Gill et al (1999). The distinctive progressive blackening and necrotic morphology of developing Matsutake mycorrhizal roots illustrated here, is perhaps influenced by a shift in the trophic status of T. matsutake as the association matures (Wang et al, 1997).…”
Section: mentioning
confidence: 53%
See 2 more Smart Citations
“…We have demonstrated here that T. matsutake forms an ectomycorrhizal association with its host P. densiflora, in concurrence with Yamada et al (1999) and Gill et al (1999). The distinctive progressive blackening and necrotic morphology of developing Matsutake mycorrhizal roots illustrated here, is perhaps influenced by a shift in the trophic status of T. matsutake as the association matures (Wang et al, 1997).…”
Section: mentioning
confidence: 53%
“…With regard to the internal morphology, although Yamada et al (1999) provided evidence of Hartig net development in P. densiflora mycorrhizal roots collected within a Shiro, Ogawa (1985) reported that such colonized roots lack both a mantle and Hartig net, although hyphae were seen to invade the intercellular spaces of the host outer cortex. The presence, in the mycorrhizal roots investigated here, of extraradical mycelium (Fig.…”
Section: mentioning
confidence: 99%
See 1 more Smart Citation
“…There are large differences in the morphology of its fruit bodies (Riva 2003) and mycorrhizas (Agerer 1987(Agerer -2002Yamada et al 1999aYamada et al , 2001b. Species used in the present study belong to three different sectoins sensu Riva (2003), i. e., T. saponaceum is in section Rigida, T. portentosum in section Equestria, and T. terreum in section Atrosquamosa.…”
Section: Discussionmentioning
confidence: 96%
“…Other reports of in vitro synthesis lack sufficient anatomical description to determine whether T. matsutake formed ecto-or endomycorrhizas (Hiromoto, 1963;Tominaga, 1963;Yokoyama and Yamada, 1987;Eto, 1990;. On the other hand, Yamada et al (1999) described natural T. matsutake ectomycorrhizas associated with P. densiflora, and resolved questions about the nature of the mycorrhizas under field conditions, i.e., whether they are ecto-, ectendo-, or pseudomycorrhiza, or have a parasitic nature (Ogawa, 1985;Smith and Read, 1997;Wang et al, 1997). These contradictory opinions about T, matsutake mycorrhizas between in vitro and in the field conditions raise questions about the ecophysiology of this fungus from the view points of both basic and applied biology.…”
mentioning
confidence: 97%